2024
DOI: 10.1001/jamaoncol.2023.5013
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Osimertinib for Previously Untreated Patients With NSCLC and Uncommon EGFR Mutations

Yusuke Okuma,
Kaoru Kubota,
Mototsugu Shimokawa
et al.

Abstract: ImportanceNon–small cell lung cancer (NSCLC) with uncommon EGFR mutations is a rare subgroup, composing 14% of all EGFR mutations.ObjectiveTo determine the usefulness of osimertinib in previously untreated patients with metastatic NSCLC harboring uncommon EGFR mutations, excluding exon 20 insertion mutations.Design, Setting, and ParticipantsThis multicenter, open-label, single-group, phase 2 nonrandomized clinical trial enrolled patients from April 10, 2020, to May 31, 2022, with a follow-up of 6 months from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Similarly, the rare S768I mutation in EGFR exon 20 has also been shown to have the longest PFS of 14.7 months. Recently, both a retrospective and prospective phase 2 non-randomised study (UNICORN) demonstrated clinical activity of osimertinib in uncommon EGFR mutations with an ORR of up to 66% ( 9 , 10 ). Despite this, none of the trials included patients with EGFR exon 18 deletion-insertion (p.E709_T710) which resulted in our decision to utilise osimertinib instead of afatinib based on its superior intracranial efficacy and favourable side effect profile.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the rare S768I mutation in EGFR exon 20 has also been shown to have the longest PFS of 14.7 months. Recently, both a retrospective and prospective phase 2 non-randomised study (UNICORN) demonstrated clinical activity of osimertinib in uncommon EGFR mutations with an ORR of up to 66% ( 9 , 10 ). Despite this, none of the trials included patients with EGFR exon 18 deletion-insertion (p.E709_T710) which resulted in our decision to utilise osimertinib instead of afatinib based on its superior intracranial efficacy and favourable side effect profile.…”
Section: Discussionmentioning
confidence: 99%
“…ESMO Open (2023) 40 Phase II 17/17 17 17/2/0 47% (23% to 72%) 8.7 (1.9-13.9) 94% (71% to 100%) 10.5 (3.7-15.2) 47% (23% to 72%) 0% Okuma et al. JAMA Oncol (2024) (UNICORN—Japan) 41 Phase II 40/40 40 32/8/7 55% (38.5% to 70.7%) 22.7 (9.5-NR) 90% (76.3% to 97.2%) 9.4 months (3.7-15.2) 53.1% (36% to 69%) 75% (41% to 93%) Major uEGFR: G719X, L861X, and S768I; minor uEGFR: any EGFR alteration other than major uEGFR, T790M, and classical EGFR mutations. CI, confidence interval; DCR, disease control rate; DOR, duration of response; EGFR, epidermal growth factor receptor; mPFS, median progression-free survival; NA, not available; NR, not reached; NSCLC, non-small-cell lung cancer; ORR, overall response rate; TKI, tyrosine kinase inhibitor; uEGFR, uncommon alterations of EGFR .…”
Section: Discussionmentioning
confidence: 99%
“…For NSCLC with uncommon point mutations in EGFR, osimertinib yielded a 55% response rate and a median progression-free survival (PFS) of 9.4 months in the single-arm phase II UNICORN study. 13 The EGFR variants in the 40 evaluable patients included E709X, G719X, S768I, and L861Q, which are among the most frequently described uncommon mutations. In a phase III study of 109 previously untreated patients with advanced NSCLC and uncommon EGFR point mutations (excluding de novo T790M), afatinib demonstrated superior PFS (median 10.5 v 5.7 months; hazard ratio, 0.422; P 5 .0007) and a numerically higher response rate (61.4% v 47.1%, P 5 .2069) compared with platinum doublet chemotherapy (ACHILLES/TORG1834).…”
Section: Introductionmentioning
confidence: 99%